THE APPLICATION OF ELECTRONIC MULTIMEDIA RESOURCES FOR STUDENTS IN PHYSICS LEARNING - Dehqonova, Ohista; Taylanov, Nizom (Физико-технологического образование, 2022)
The main task of this paper is study the problem of organizing the educational process or to establish electronic online communication between student and teacher, to include in the site teaching materials for teachers, to provide students with this to work on data and to use other distance learning services. Multimedia tools are a set of hardware and software that allows a person to communicate with a computer using a variety of environments that are natural to him: sound, video, graphics, text, animation, and more